2022
DOI: 10.3390/en15103570
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Balance between Heating, Cooling and Environmental Impacts: A Method for Appropriate Assessment of Building Envelope’s U-Value

Abstract: In Europe, the recent application of regulations oriented to zero-energy buildings and climate neutrality in 2050 has led to a reduction in energy consumption for heating and cooling in the construction sector. The thermal insulation of the building envelope plays a key role in this process and the requirements about the maximum allowable thermal transmittance are defined by country-specific guidelines. Typically, high insulation values provide low energy consumption for heating; however, they may also entail … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 22 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…In the case of buildings with permanent use, the optimal thermal insulation thickness is consistently 12 cm across all types of HVAC system control, temperate Mediterranean climates, and climate change scenarios. This arises from the fact that, for these types of buildings (with low internal thermal loads) and passive constructive elements (with high thermal mass), the increasing of thermal insulation thickness leads to a decrease of energy consumption for heating and an increase of energy consumption for cooling, as shown by the results of this study (figures not shown) and what is reported in the bibliography [10,20,30,42]. Additionally, with the increase of thermal insulation thickness, the rate of decrease in energy consumption for heating is greater than the rate of increase in consumption for cooling, which is reflected in a continuous decrease in energy consumption for air conditioning.…”
Section: Optimal Thermal Insulation Thickness and External Shades Lengthmentioning
confidence: 52%
See 1 more Smart Citation
“…In the case of buildings with permanent use, the optimal thermal insulation thickness is consistently 12 cm across all types of HVAC system control, temperate Mediterranean climates, and climate change scenarios. This arises from the fact that, for these types of buildings (with low internal thermal loads) and passive constructive elements (with high thermal mass), the increasing of thermal insulation thickness leads to a decrease of energy consumption for heating and an increase of energy consumption for cooling, as shown by the results of this study (figures not shown) and what is reported in the bibliography [10,20,30,42]. Additionally, with the increase of thermal insulation thickness, the rate of decrease in energy consumption for heating is greater than the rate of increase in consumption for cooling, which is reflected in a continuous decrease in energy consumption for air conditioning.…”
Section: Optimal Thermal Insulation Thickness and External Shades Lengthmentioning
confidence: 52%
“…Various methodologies exist for classifying the different climate types. Among these, the approach based on heating degree-days (HHD [ºC•day/year]) and cooling degree-days (CDD [ºC•day/year]) provides a more direct link between outdoor weather conditions and energy requirements for heating and cooling, respectively [7,30,42].…”
Section: Climate Scenariosmentioning
confidence: 99%
“…Building envelope thermal properties were normalized based on common values found in the literature ( Table 3 ). 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 The normalized envelope system has a value of 0, which indicates that the envelope has the best performance found in literature, with the best thermal insulation for walls, roofs, and fenestrations, 42 while a value of 1 indicates that the building envelope is not well insulated. 43 …”
Section: Resultsmentioning
confidence: 99%
“…The surface thermal resistances only depend on the surface characteristics and wind speed conditions [6]. Therefore, thermal losses can be greatly impacted by the first centimetres of insulation, but after a certain thickness, the effect on the overall resistance of the component is no longer expressive [7][8][9][10][11]. Many studies [7][8][12][13][14][15][16][17], evaluated the optimum in-sulation thickness, yet with an economic approach, disregarding the energy used for producing and transporting insulation materials, the so-called grey energy aspect and the related carbon emissions.…”
mentioning
confidence: 99%
“…Furthermore, [18] proposes a mathematical model to evaluate the impact of grey energy of ever-increasing insulation thicknesses on energy savings. [10] shows that depending on the climate and the mass of the wall, when considering the grey energy of a generic high standard insulation material, the optimal U-value is not necessarily the lowest. Our study investigates the impact of four types of insulation materials on energy savings over the life cycle of the building, depending on their thickness.…”
mentioning
confidence: 99%